Alteration in Oxidative Stress Enzymes and Proteins by Datura metel Stramonium Hydroethanolic Root Extract Promotes Hippocampus and Cerebral Cortex Neurons Damage in Adult Sprague Dawley Rats - oboma YI; Eberechukwu GC (Substance Abuse and Rehabilitation)
Yibala Ibor oboma,1,2 God’sman C Eberechukwu1,3 1Department of Medical Laboratory Science, Faculty of Basic Medical Sciences, College of Health Sciences, Niger Delta University Wilberforce Island Bayelsa State, Amassoma, Nigeria; 2Department of Medical Laboratory Science, School of Allied Health Sciences, Kampala International University, Ishaka Municipal, Uganda; 3Department of Histopathology and Cytopathology, Faculty of Medical Laboratory Science, Federal University, Otuoke, Bayelsa State, NigeriaCorrespondence: Yibala Ibor oboma, Department of Medical Laboratory Science, School of Allied Health Sciences, Kampala International University, Western Campus, Bushenyi District, Ishaka Municipal, Uganda, Tel +256740059020, Email yibaaoboma@kiu.ac.ugBackground: Datura metel is reported to induce hallucinations and mental disorders.Objective: This study investigates the neurotoxic effects of Datura metel stramonium hydroethanolic root extract on the hippocampus and cerebral cortex of adult rats using biochemical, histological and immunohistochemical techniques.Methodology: Twenty five adult rats were assigned to 5 groups (n = 5 each). Group A - negative control, group B (lead positive control). Groups C, D, and E exposed to 150 mg/kg, 300 mg/kg and 600 mg/kg body weight of extracts for 14 days once daily, respectively. Histology, biochemistry and immunohistochemical techniques were used to study cell injury in the brain tissue.Results: Biochemical alterations were observed in superoxide dismutase (SOD), Malondialdehyde (MDA), Glutathionine S-transferase (GST) and Catalase among the experimental groups. Catalase was statistically significant at P< 0.05. Histology reveals neurons damage, depletion and vacuolation. NFP and NSE were over expressed in the experimental groups.Discussion: Oral administration of Datura metel root extracts at high concentration alters the antioxidant enzymes activity and body weight. Extracts cause cortex and hippocampus neurotoxicity through heightened oxidative stress.Conclusion: Datura metel root extract is a neurotoxic agent and causes depopulation of hippocampus and cerebral cortex neurons. The use of this plant should be highly regulated to reduce neuropathies associated with consumption.Keywords: Datura metel, oxidative stress, neuronal damage